Energy Performance Contracting Initiative in Malaysian Public Hospitals - Imran, Muhammad Syukri; Abd Rahman, Noor Muhammad; Mohamed, Roslan (International Journal of Integrated Engineering, 2020)
Ministry of Health Malaysia (MOH) has integrated sustainability program in the management of its assets particularly hospital buildings in line with the national sustainability goals and the United Nation Sustainable Development Goals.  The fundamental sustainability change is significant since 2015 in the public healthcare sector where green business practice is more appreciable through formation of policy and sustainability related programme. Public hospital in Malaysia are very high energy consumers, therefore various energy projects have been implemented through Energy Performance Contracting (EPC). EPC projects in MOH is intended to deliver energy expenditure savings as well as to offset hospital building carbon footprint. EPC practice in government hospitals have managed to offset about 15.7 ktonne carbon emission in 2019 or about 16% of Government building national emission reduction target. Energy project such as energy efficient chiller retrofit, LED lighting retrofit and solar thermal hot water are some of the EPC initiatives by MOH in public hospitals. The energy projects not only serve to meet the overall Hospital Facility Management Contract sustainability goals but also to complement the green building target for Malaysian Healthcare building by 2025.  The aim of this paper is to review the development of the EPC projects in public healthcare sector and its impact on government energy spending as well as to the climate.